Academic Literacies as Cornerstones in Course Design: A Partnership to Develop Programming for Faculty and Teaching Assistants - Bury, Sophie; Sheese, Ron (Journal of University Teaching and Learning Practice, 2016)
We discuss an educational development approach to embedding academic literacies instruction within disciplinary curricula. This developmental, embedded approach contrasts with the generic, extra-curricular, study-skills approach adopted in many universities. Learning Commons partners at York University, including librarians, writing instructors, and learning skills counsellors, collaborated with educational developers in the York Teaching Commons to design a program for course instructors and teaching assistants (TAs) who seek to improve their students’ academic literacies. This program includes interactive workshops focusing on strategies to facilitate the redesign of courses and assignments so as to give explicit attention to process-related practices and abilities involved in library research and writing. The academic theory underpinning this program is outlined along with its key content elements. We also describe how the program draws on SPARK (Student Papers and Academic Research Kit), an online resource, created by the York Learning Commons under a Creative Commons license with the goal of helping students succeed with written academic assignments. Feedback from instructors and TAs support that the program has played an important role in helping them to question their assumptions and redesign their teaching practice.